Adverse effects of topical glucocorticosteroid preparations applied in dermatology - Czarnecka-Operacz, Magdalena; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Glucocorticosteroids are one of the most important group of medications used in the treatment of allergic, autoimmune and proliferative skin disorders. This paper presents the basic mechanism of action and adverse effects of glucocorticosteroids which may be expected in case of chronic and uncontrolled treatment.